Bifidobacterium bifidum presents on the cell surface a complex mixture of glucans and galactans with different immunological properties. (15th August 2019) - Speciale, Immacolata; Verma, Ravi; Di Lorenzo, Flaviana; Molinaro, Antonio; Im, Sin-Hyeog; De Castro, Cristina
Graphical abstract: Highlights: Bifidobacterium bifidum PRI1 produces a mixture of cell surface polysaccharides. Both neutral and anionic polysaccharides have different immune-regulatory activity. Neutral polysaccharides exert an immunosuppressive action on dendritic cells. Anionic polysaccharides exerted a pro-inflammatory activity on dendritic cells. Abstract: The chemical structure of cell surface polysaccharides isolated from Bifidobacterium bifidum strain PRI1, an important member of the gut microbiota of breast-fed infants, has been elucidated by chemical and NMR spectroscopy analysis. Results demonstrated that the bacterium produces a complex mixture of polysaccharides that could be classified in two main groups: a phospho-glycero-β-galactofuranan, PGβG, and a mixture composed of four neutral polysaccharides named as (CSGG), composed of β-(1 → 6)-glucan, β-(1 → 4)-galactan, β-(1 → 6)-galactan, β-galactofuranan and starch. These two fractions exerted different immune responses when assayed on dendritic cells: PGβG enhanced pro-inflammatory immune responses by increasing interferon-γ levels while CSGG induced immunosuppressive regulatory T cells and interleukin-10. These findings demonstrate that bacterial polysaccharides have a distinct role depending on their chemical structure in regulation of the host/bacterium interaction. Our findings suggest that polysaccharides may differentially regulate the host immunity depending on the composition of this complex mixture, either enhancing immunity or inducing immune tolerance.